2002
DOI: 10.1164/rccm.2110093
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations and Mortality in the Lung Health Study

Abstract: This report deals with deaths and hospitalizations during the 5-year Lung Health Study, as documented by examination of appropriate records. There were 149 deaths (2.5%) during the study, caused largely by lung cancer and cardiovascular disease, particularly coronary heart disease. A total of 12.8% of participants were hospitalized, with cancer, cardiovascular disease, and nonmalignant respiratory disease accounting for 75% of hospitalizations. There were no significant differences among the original treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
338
0
44

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(390 citation statements)
references
References 10 publications
8
338
0
44
Order By: Relevance
“…Biological plausibility is also suggested by the observation that ipratropium bromide increases cardiovascular risk, thereby suggesting that the increase in risk may represent a class effect of inhaled anticholinergic agents. This was originally observed in the Lung Health Survey, in which the regular use of ipratropium bromide by metered dose inhaler increased the risk of cardiovascular death, RR 2.57 (95% CI 1.12-6.62) [36]. Ipratropium bromide was also noted to increase the risk of hospital admission due to arrhythmias with a relatively high prevalence of supraventricular tachycardia.…”
Section: Biological Plausibilitymentioning
confidence: 73%
“…Biological plausibility is also suggested by the observation that ipratropium bromide increases cardiovascular risk, thereby suggesting that the increase in risk may represent a class effect of inhaled anticholinergic agents. This was originally observed in the Lung Health Survey, in which the regular use of ipratropium bromide by metered dose inhaler increased the risk of cardiovascular death, RR 2.57 (95% CI 1.12-6.62) [36]. Ipratropium bromide was also noted to increase the risk of hospital admission due to arrhythmias with a relatively high prevalence of supraventricular tachycardia.…”
Section: Biological Plausibilitymentioning
confidence: 73%
“…5,8,11,24 The relatively low mortality rate is likely due to the fact that patients were recruited from outpatient clinics, not from hospitals settings 25 where mortality rates can be up to 49% at 2 years. 26 FEV 1% had the strongest association with mortality in our study, a relationship that has been observed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that most COPD patients die from causes other than COPD. In mild COPD in the Lung Health Study [7], the largest single cause was actually lung cancer. In the present study, death from ischaemic heart disease was more frequent; however, among subjects with COPD, death from lung cancer made up 10% of all deaths.…”
Section: Discussionmentioning
confidence: 99%
“…From the American National Health and Nutrition Examination Survey (NHANES), it seems that not only mild but also moderate and severe stages of COPD are underdiagnosed [3]. There are few data available concerning underestimation of COPD as cause of death; in fact, only relatively few studies have focused on causes of death in COPD [4][5][6][7][8] and several of them have selected populations. Very little is known about the validity of mortality statistics in COPD.…”
mentioning
confidence: 99%